Effect of diet on male reproductive tract of Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) - Lemos, W. P; Serrão, J. E; Ramalho, F. S; Cola Zanuncio, J. C.; Lacerda, M. C. (Brazilian Journal of Biology, 2005)
The morphology and histology of the reproductive tract of males of the predator Podisus nigrispinus (Dallas) fed on different diets were studied. P. nigrispinus was fed on diets of: larvae of Alabama argillacea (Hübner), Tenebrio molitor L., Musca domestica L., and an artificial diet. The male reproductive tract, independent of diet, showed testes with intense red coloration in a compact, circular, or slightly oval structure. The vasa deferentia were similar in color to the testes and formed long filaments, which joined with the yellow-cream colored ejaculatory duct. The morphological characteristics of the male reproductive tract were similar under all diets, except for the artificial one. The histological studies demonstrated that independent of the diet the testes of P. nigrispinus were composed of four to six follicles. The testes with six follicles generally had four developed and two atrophied follicles. The morphological and histological differences of the testes of P. nigrispinus when fed with different prey are presented and discussed.

Estudou-se a morfologia e a histologia do órgão reprodutivo de machos do predador Podisus nigrispinus (Dallas), alimentados com diferentes dietas (lagartas de Alabama argillacea (Hübner), larvas de Tenebrio molitor L., larvas de Musca domestica L. e dieta artificial). O órgão reprodutivo dos machos, independentemente da dieta fornecida, apresentou testículos com coloração vermelha intensa, compactos e de aspecto circular ou ligeiramente ovóide. Os canais deferentes apresentaram coloração semelhante a dos testículos e forma de filamentos longos, os quais se conectam a um duto ejaculatório de coloração creme-amarelada. As características morfológicas do órgão reprodutivo dos machos foram similares em todas as dietas, exceto quando alimentados com dieta artificial. Os estudos histológicos demonstraram que, independentemente da dieta, os testículos de P. nigrispinus são compostos por quatro a seis folículos. Os testículos com seis folículos geralmente têm quatro folículos desenvolvidos e dois atrofiados. Este trabalho apresenta e discute as diferenças morfológicas e histológicas dos testículos de P. nigrispinus alimentados com as diferentes dietas.
Keywords: Asopinae; Biological control; Morphology; Testis; Predator